2018
DOI: 10.5194/amt-11-5781-2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the performance of a ship-borne scanning wind lidar in the Arctic and Antarctic

Abstract: Abstract. In the present study a non-motion-stabilized scanning Doppler lidar was operated on board of RV Polarstern in the Arctic (June 2014) and Antarctic (December 2015–January 2016). This is the first time that such a system measured on an icebreaker in the Antarctic. A method for a motion correction of the data in the post-processing is presented. The wind calculation is based on vertical azimuth display (VAD) scans with eight directions that pass a quality control. Additionally a method for an empirical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…ERA5 and ERA-Interim show similar values. This good agreement could stem partially from the fact that the radio soundings of the ship (2-3 d −1 ) are assimilated in ERA5 and ERA-Interim, which show also good agreement with the lidar data (Zentek et al, 2018). The computation of the statistics for different heights showed that the wind speed RMSE of CCLM is largest around a height of 1000 m, while the RMSE of ERA5 and ERA-Interim is mostly constant with height ( Fig.…”
Section: Overall Statisticssupporting
confidence: 54%
See 3 more Smart Citations
“…ERA5 and ERA-Interim show similar values. This good agreement could stem partially from the fact that the radio soundings of the ship (2-3 d −1 ) are assimilated in ERA5 and ERA-Interim, which show also good agreement with the lidar data (Zentek et al, 2018). The computation of the statistics for different heights showed that the wind speed RMSE of CCLM is largest around a height of 1000 m, while the RMSE of ERA5 and ERA-Interim is mostly constant with height ( Fig.…”
Section: Overall Statisticssupporting
confidence: 54%
“…Benefits of modelling a fractional sea ice cover are investigated in Gutjahr et al (2016). As daily sea ice thickness data like PIOMAS (Zhang and Rothrock, 2003) are not available for Antarctica, we assume two different ice classes depending on the initial sea ice concentration. Grid points with a sea ice concentration of 0 %-15 % are set to open water.…”
Section: Cclmmentioning
confidence: 99%
See 2 more Smart Citations
“…We installed a Doppler lidar onboard the RV Polarstern and measured vertical profiles of horizontal wind speed and direction from 24th December till 30th January. In Zentek et al (2018) we compared the measurements to radio soundings and ship measurements and found a bias (root mean square deviation) of approx. 0.1 (1) ms −1 for wind speed and 1 (10)°for wind direction, respectively.…”
Section: Lidarmentioning
confidence: 99%